PEMBELAJARAN SENI MUSIK DENGAN MEDIA AUDIO VISUAL YOUTUBE BAGI SISWA KELAS IV SD NEGERI 1 BULUROTO - Noorvita Murdyanti; Ari Widyaningrum; Sunan Baedowi (STKIP Subang, 2023)
The context of this research is based on the learning process which cannot be separated from the learning media. Learning media is a teacher's tool to make it easier to convey material information to students. The research focus that drives this research is